Rancang Bangun Sistem Informasi Kontrol Kondisi Lalu Lintas Dengan Kamera Pemantau Cctv Berbasis Gis - Trenggono, Erik Priyo; Sukmaaji, Anjik; Taufik, Vicky M (Jurnal JSIKA, 2012)
Congestion that occurred in Indonesia, especially the metropolitan cities like Jakarta, Bandung, and Surabaya became the main things that become problems in large cities. This resulted in losses for many of the users of transport such as time, cost, health, and environment. CCTV cameras already spread by the transport department and police, but CCTV is recording and the staff determines that whether the CCTV cameras mounted road occurs road conditions experienced congestion or an accident. This is have weakness, officers should standby at any time to view the situation of the road. From the facts that occurred, the use of decision support systems are important in determining the condition of roads that have been installed CCTV cameras. Utilization of the support system can give way to overcome problems of congestion, it allows officers in responding to traffic conditions and the impact of congestion. So that decision-making processes can make effective and efficient officer where the officer did not waste any time to monitor the CCTV cameras at any time and reduce errors target the implementation of alternative path selection.   Keywords : Decision Support Systems, Digital Imaging, SMS Gateway, Intelligent Transport System, Geographic Information Systems, Traffic Control, CCTV, Monitoring Camera.